Implementation of Strategies in Management of Change To Achieving Quality Levels of Service to Consumers (Case Study on Shopee Application Company) - Muslimatul Husnah; Nuri Aslami (Penerbit Jurnal Indonesia, 2022)
Huge business opportunities such as product sales and online service provision and revenue growth for companies such as e-retailers are primarily due to their easy and interactive nature, lower costs, and high level of customization and personalization for customers. This research is intended to analyze service quality and consumer satisfaction of Shopee e-commerce application users. The purpose of this study is to be able to analyze how the strengths, weaknesses, opportunities and threats of using the shopee online store are. The research conducted is qualitative. The data collection using the distribution of questionnaires. Many consumers complain about the cycle of service and satisfaction levels in the Shopee application, both directly and indirectly. As it is known that making changes is not an easy thing for organizations, because all systems or some systems that will be changed automatically, members of the organization must also adapt to things that are not necessarily well received, therefore in the process of change there needs to be good management. whether done by the leader of the Shopee Application, there are things that must be done strategically in overcoming resistance well to ensure that a change will go well. So there is a lot that must be prepared before making changes, to improve the quality of service to consumers again.